2020
DOI: 10.3389/fneur.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Central Adaptation in Benign Paroxysmal Positional Vertigo

Abstract: Objective: To elucidate the frequency, underlying mechanisms, and clinical implications of spontaneous reversal of positional nystagmus (SRPN) in benign paroxysmal positional vertigo (BPPV). Methods: We prospectively recruited 182 patients with posterior canal (PC, n = 119) and horizontal canal (HC) BPPV (n = 63) canalolithiasis. We analyzed the maximal slow phase velocity (maxSPV), duration, and time constant (Tc) of positional nystagmus, and compared the measures between groups with and without SRPN. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…In this study, among 575 consecutive patients with benign paroxysmal positional vertigo, 54 of 575 (9.39%) patients with reversal nystagmus were identified, of which 5.56%(32 of 575) had horizontal semicircular canal BPPV and 3.82% (22 of 575) had posterior semicircular canal BPPV. Compared with previous studies (the incidence of patients with horizontal semicircular canal BPPV reversal nystagmus was 73%) (8,12), the incidence of reversal nystagmus in BPPVobserved in our study was lower (68%). However, a similar result was reported in a study from Japan showing that the incidence of reversal nystagmus in patients with horizontal semicircular canal BPPV was 10% (7).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In this study, among 575 consecutive patients with benign paroxysmal positional vertigo, 54 of 575 (9.39%) patients with reversal nystagmus were identified, of which 5.56%(32 of 575) had horizontal semicircular canal BPPV and 3.82% (22 of 575) had posterior semicircular canal BPPV. Compared with previous studies (the incidence of patients with horizontal semicircular canal BPPV reversal nystagmus was 73%) (8,12), the incidence of reversal nystagmus in BPPVobserved in our study was lower (68%). However, a similar result was reported in a study from Japan showing that the incidence of reversal nystagmus in patients with horizontal semicircular canal BPPV was 10% (7).…”
Section: Discussioncontrasting
confidence: 88%
“…In 2015, Ogawa et al (7) proposed that the coexistence of cupulolithiasis and canalolithiasis may be a mechanism that could explain the generation of bilateral reversal nystagmus. In 2020, Choi et al (8) proposed central adaptation mechanism to elucidate the generation of reversal nystagmus. Since the phenomenon of reversal nystagmus in BPPV was discovered, several mechanistic hypotheses have been proposed; however, no theory can explain the occurrence of reversal nystagmus perfectly.…”
Section: Introductionmentioning
confidence: 99%
“…Four patients showed an evolution of initial positional downbeat into upbeat nystagmus over 4-15 s. This reversal in the direction of induced nystagmus is observed in various conditions including benign paroxysmal positional vertigo (22)(23)(24), head-shaking nystagmus (25), caloric stimulation (26), and vertebral artery occlusion syndrome (21), and may be ascribed to short-term adaption of the vestibular imbalance.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the incidence of direction-reversing nystagmus was also significantly higher in the CS-BPPV group compared with that in the NCS-BPPV group. A previous study showed that direction-reversing nystagmus during position tests may be caused by short-term central adaptation following the intense first phase nystagmus ( 22 ). This suggests that the high SPV observed in the CS-BPPV group is not accidental.…”
Section: Discussionmentioning
confidence: 99%